Polycotton waste textile recycling by sequential hydrolysis and glycolysis - Nienke Leenders; Rijk M. Moerbeek; Matthijs J. Puijk; Robbert J. A. Bronkhorst; Jorge Bueno Morón; Gerard P. M. van Klink; Gert-Jan M. Gruter (Nature Communications)
Abstract As a result of the current high throughput of the fast fashion collections and the concomitant decrease in product lifetime, we are facing enormous amounts of textile waste. Since textiles are often a blend of multiple fibers (predominantly cotton and polyester) and contain various different components, proper waste management and recycling are challenging. Here, we describe a high-yield process for the sequential chemical recycling of cotton and polyester from mixed waste textiles. The utilization of 43 wt% hydrochloric acid for the acid hydrolysis of polycotton (44/56 cotton/polyester, room temperature, 24 h) results in a 75% molar glucose yield from the cotton fraction, whereafter the hydrolysate solution is easily separated from the solid polyester residue. The reaction is scalable, as similar results are obtained for experiments performed at 1 mL, 0.1, and 1.0 L and even in a 230 L pilot plant reactor, where mixed postconsumer polycotton waste textile is successfully recycled. The residual polyester is successfully converted via glycolysis to bis(2-hydroxyethyl) terephthalate in 78% isolated yield (>98% purity).